54. The Geology of the Ore Deposits of the Pioche District, Nevada - Paul Gemmill (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
Production was first recorded from the Pioche district in 1864, and it has continued to show an inherent ability to take on new life after periods of depression in the metal markets. Production from replacement leadsilver- zinc sulfide ore bodies in limestones of Cambrian age now accounts for several times the gross value of silver production from rich fissures in Lower Cambrian Quartzite. Aggregate production of some 6 million tons represents a gross value over $100-million. Future output is expected mostly to be from limestone replacement deposits of which the most productive are "channels" of ore up to several hundred feet wide and several thousand feet long with thicknesses from a few feet up to 50 feet. Such channels are restricted to the lowermost limestone bed of the district, about 250 feet above the basement quartzite. The "blotter-like" characteristic of this highly productive Jimesto~e bed in absorbing mineralization is believed to be, at least in part, due to lithology, including free carbon in the bed, which has created a unique set of conditions for delicately balanced mineralizing solutions that rejected any tendency to replace siliceous wall rock and were properly constituted for replacement of Limestone. All recognizable orogenic history is considered to be related to the Basin and Range faulting that created the mountain ranges. The faults developed after mid-Tertiary time and after widespread extrusives that are themselves involved in the faulting. Flat faults, formerly believed to be part of regional thrust faulting, are now interpreted as gravity slide faulting that can be shown to be large in magnitude and not simply local landslides. Large slide faults generally have concealed the great magnitude of mountain-bordering faults. Mineralization that accounts for ore is later than the faulting. Most faults are pre-mineral since they influence the shape of ore bodies, and some clearly have been offset by fault fissures containing ore. Post-mineral movement probably has been an important component of some large, initially pre-mineral faults. A single period of mineralization was begun by the introduction of large quantities of ironmanganese carbonate, and, in places, carbonate manganese with minor values in sulfides. Closely following the carbonate invasion, massive sulfides were brought in, usually replacing part of the carbonate body though in some places the massive sulfides replaced limestone that was not previously mineralized. Manganese mineralization is not a "halo" but leaks of manganese to higher formations and to the surface are the most significant exploration guides. The Pioche district is expected to be long lived with technological developments in ore treatment being important to the exploitation of low-grade manganiferous ores, while aggressive exploration is expected to find important quantities of bedded lead-silver-zinc ores of the massive sulfide type.